The Case of the Errant Executive: Management, Control and Firm Size in Corporate Cheating - GUHA, Brishti (Institutional Knowledge at Singapore Management University, 2005)
Firm insiders – a manager and a board – face moral hazard in relation to their outside shareholders in a repeated game with asymmetric information and stochastic market outcomes. The manager determines whether or not outsiders are cheated; the board, whose objectives differ from those of outside shareholders, attempts to control the manager through compensation contracts and dismissal threats Since compensation determines the manager’s incentive to cheat, firms competing for outside capital publicly announce their managerial contracts. However, secret renegotiation between firm and manager is still possible: so outsiders guard against being cheated by limiting their total stake in any firm. This imposes a credibility constraint on firm size, providing a rationale for the shape of long-run cost curves. Given this limit on outside funds, the minimum size requirement for enterprises to become operational and the ability to pay managers enough to ensure honesty both set a floor to the personal wealth required to enter entrepreneurship. Thus, we endogenize entry into industry, establish a unique equilibrium for any distribution of wealth, and characterize different equilibria. We also explain features of poor countries like dominance of family firms, moral hazard induced vicious circles that retard industrialization and the stimulus that inequality may provide to industrial development.